Guideline of transthyretin-related hereditary amyloidosis for clinicians - Ando, Y. (2013)
Transthyretin amyloidosis is a progressive and eventually fatal disease primarily characterized by sensory, motor, and autonomic neuropathy and/or cardiomyopathy. Given its phenotypic unpredictability and variability, transthyretin amyloidosis can be difficult to recognize and manage. Misdiagnosis is common, and patients may wait several years before accurate diagnosis, risking additional significant irreversible deterioration. This article aims to help physicians better understand transthyretin amyloidosis—and, specifically, familial amyloidotic polyneuropathy—so they can recognize and manage the disease more easily and discuss it with their patients. We provide guidance on making a definitive diagnosis, explain methods for disease staging and evaluation of disease progression, and discuss symptom mitigation and treatment strategies, including liver transplant and several pharmacyotherapies that have shown promise in clinical trials.